High throughput LC–MS/MS method for the simultaneous analysis of multiple vitamin D analytes in serum - Jenkinson, Carl; Taylor, Angela E.; Hassan-Smith, Zaki K.; Adams, John S.; Stewart, Paul M.; Hewison, Martin; Keevil, Brian G. (Journal of chromatography. B, Analytical technologies in the biomedical and life sciences, 2016)
•High throughput LC–MS/MS method to measure multiple vitamin D metabolites in serum.•SLE is an effective sample preparation method for multiple vitamin D metabolites.•Chiral column separation improves resolution between identical mass to charges.•Routine serum analysis shows correlations between active and inactive metabolites. Recent studies suggest that vitamin D-deficiency is linked to increased risk of common human health problems. To define vitamin D ‘status’ most routine analytical methods quantify one particular vitamin D metabolite, 25-hydroxyvitamin D3 (25OHD3). However, vitamin D is characterized by complex metabolic pathways, and simultaneous measurement of multiple vitamin D metabolites may provide a more accurate interpretation of vitamin D status. To address this we developed a high-throughput liquid chromatography-tandem mass spectrometry (LC–MS/MS) method to analyse multiple vitamin D analytes, with particular emphasis on the separation of epimer metabolites. A supportive liquid-liquid extraction (SLE) and LC–MS/MS method was developed to quantify 10 vitamin D metabolites as well as separation of an interfering 7α-hydroxy-4-cholesten-3-one (7αC4) isobar (precursor of bile acid), and validated by analysis of human serum samples. In a cohort of 116 healthy subjects, circulating concentrations of 25-hydroxyvitamin D3 (25OHD3), 3-epi-25-hydroxyvitamin D3 (3-epi-25OHD3), 24,25-dihydroxyvitamin D3 (24R,25(OH)2D3), 1,25-dihydroxyvitamin D3 (1α,25(OH)2D3), and 25-hydroxyvitamin D2 (25OHD2) were quantifiable using 220μL of serum, with 25OHD3 and 24R,25(OH)2D3 showing significant seasonal variations. This high-throughput LC–MS/MS method provides a novel strategy for assessing the impact of vitamin D on human health and disease.